2011
DOI: 10.1007/s00464-011-1689-y
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of proton pump inhibitors versus laparoscopic Nissen fundoplication for patients with gastroesophageal reflux disease: a systematic review of the literature

Abstract: The results with regard to cost-effectiveness are inconclusive. All four economic models are based on high- and low-quality data. More reliable estimates of cost-effectiveness based on long-term trial data are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
5
0
2
Order By: Relevance
“…Also, wide variability in outcomes has limited the adoption of this procedure [Richter and Dempsey, 2008;Vakil et al 2003]. A Cochrane analysis found that laparoscopic fundoplication surgery is more effective than medical management for the treatment of GERD in short-to medium-term follow up [Wileman et al 2010], although studies on the cost effectiveness of Nissen fundoplication versus pharmacological therapy with PPIs have been largely inconclusive [Thijssen et al 2011].…”
Section: Comparison Of Current Therapeutic Options For Gastroesophagementioning
confidence: 99%
“…Also, wide variability in outcomes has limited the adoption of this procedure [Richter and Dempsey, 2008;Vakil et al 2003]. A Cochrane analysis found that laparoscopic fundoplication surgery is more effective than medical management for the treatment of GERD in short-to medium-term follow up [Wileman et al 2010], although studies on the cost effectiveness of Nissen fundoplication versus pharmacological therapy with PPIs have been largely inconclusive [Thijssen et al 2011].…”
Section: Comparison Of Current Therapeutic Options For Gastroesophagementioning
confidence: 99%
“…As the goal is improved quality of life, the increased in cost should be offset by a distinct gain in symptom control and/or decrease in health‐care resource utilization. A review of available data concluded that studies addressing cost‐effectiveness of operative and medical therapy for patients with gastroesophageal reflux are inconclusive . Modeling studies including quality of life changes point at a potential for cost savings only if the symptomatic benefit persists .…”
Section: Discussionmentioning
confidence: 99%
“…A review of available data concluded that studies addressing cost-effectiveness of operative and medical therapy for patients with gastroesophageal reflux are inconclusive. 39 Modeling studies including quality of life changes point at a potential for cost savings only if the symptomatic benefit persists. 40 However, current evidence indicates that most patients will continue or restart acid suppressive medication after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery also eliminates the concern for patient compliance with medical therapy, and may reduce the cost of treatment compared with life-long antisecretory therapy. 15 Approach to Antireflux Surgery for Barrett's Esophagus…”
Section: Benefits Of Antireflux Surgerymentioning
confidence: 99%